Pengaruh Motivasi Terhadap Kinerja Karyawan Kementerian Perhubungan Biro Keuangan - Sumantri, Bimo Dwiputra; Hawari, Yusmita (Jurnal Ilmiah Wahana Pendidikan, 2024)
The objective of this study was to investigate and determine the impact of motivation on the performance of employees within the Finance Bureau of the Ministry of Transportation. The study population consisted of 61 employees affiliated with the Ministry of Transportation. Utilizing a census approach, also known as a saturated sample, the entire population was included in the study as the sample, given that the population size did not exceed 100 individuals. The data collection for this research involved the utilization of quantitative data processed using SPSS. In the analysis of data, methods such as the coefficient of determination, partial test (t-test), and simple linear regression were applied. The results of the t-test, with a t-count of 5.894 > 2.023 and a significance of 0.000 < 0.005, indicated that the motivation variable exerted a significant and positive influence on employee performance. The R Square value stands at 0.495, equivalent to 49.5%, suggesting that while there are other variables or factors not considered in this study influencing the remaining 50.5% of employee performance, remuneration and workload account for a 49.5% impact.